Blow‐up of the smooth solutions to the compressible Navier–Stokes equations. (20th March 2017) - Wang, Guangwu; Guo, Boling; Fang, Shaomei
Abstract : In this paper, we will firstly extend the results about Jiu, Wang, and Xin (JDE, 2015, 259, 2981–3003). We prove that any smooth solution of compressible fluid will blow up without any restriction about the specific heat ratio γ . Then we prove the blow‐up of smooth solution of compressible Navier–Stokes equations in half space with Navier‐slip boundary. The main ideal is constructing the differential inequality. Copyright © 2017 John Wiley & Sons, Ltd.